Peran Pesantren Lansia Darus Syifa’ Jombang Dalam Meningkatkan Kesejahteraan Fisik Dan Mental Lansia - Erisa Veriany Nur Annisa; Kusumawati, Ita Rahmania; Noho, Muhammad Dzikirullah H. (Kariman: Jurnal Pendidikan Keislaman, 2024)
Senior Islamic boarding schools represent an innovative approach to elderly empowerment that can enhance the quality of life for older adults. This study aims to explore the role of Darus Syifa' Senior Islamic Boarding School in Jombang in improving the physical and mental well-being of elderly individuals. Using a qualitative research approach with a case study method, the research involved  elderly participants. Data was collected through in-depth interviews, participatory observation, and documentation. The findings reveal that Darus Syifa' Senior Islamic Boarding School significantly contributes to improving elderly welfare through religious guidance programs, social activities, and holistic health support. The boarding school's programs effectively enhance the elderly's quality of life across spiritual, psychological, and social dimensions. The research concludes that the Islamic boarding school-based elderly empowerment model can serve as an effective alternative for improving elderly well-being in Indonesia.